Method of forming reproducible and unpredictable sequence of permutations - Фауре, Еміль Віталійович; Швидкий, Валерій Васильович; Щерба, Анатолій Іванович (Ukrainian Scientific Journal of Information Security, 2014)
In this paper, we propose the method for constructing a repeatable and unpredictable sequence of permutations based on the use of positional notation with factorial base to represent syndrome of formed permutation. For the formation of syndrome of the next permutation in the sequence an additional generator of (pseudo) random decimal numbers is used. The evaluation rules of summing of decimal and factorial numbers are developed. The next implementations of the method of forming sequence of permutations are developed: with a fixed zero, with a random zero or with a modified random zero. The possibility of working with the overt and covert order of transformation of the factorial record of number into permutation and the overt and covert permutations order in real time is shown.